2010
DOI: 10.1021/jp106822s
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Magnetic Coupling of Manganese Porphyrin to a Ferromagnetic Cobalt Substrate

Abstract: The coupling mechanism of magnetic molecules to ferromagnetic surfaces is of scientific interest to design and tune molecular spintronic interfaces utilizing their molecular and surface architecture. Indirect magnetic coupling has been proposed earlier on the basis of density functional theory +U (DFT+U) calculations, for the magnetic coupling of manganese(II) porphyrin (MnP) molecules to thin Co films. Here we provide an experimental X-ray magnetic circular dichroism (XMCD) spectroscopy and scanning tunneling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
59
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 30 publications
2
59
0
Order By: Relevance
“…2(b)]. This chemical shift confirms that chlorine is detached from CrTPPCl upon adsorption and directly adsorbed on the Co substrate [16]. As also evidenced by our data, Cl does not contribute to the AFM exchange coupling between CrTPP molecules and the bare cobalt.…”
supporting
confidence: 83%
See 3 more Smart Citations
“…2(b)]. This chemical shift confirms that chlorine is detached from CrTPPCl upon adsorption and directly adsorbed on the Co substrate [16]. As also evidenced by our data, Cl does not contribute to the AFM exchange coupling between CrTPP molecules and the bare cobalt.…”
supporting
confidence: 83%
“…In "on-surface" configurations novel properties can arise when the magnetic and electronic characteristics of the metal-organic species are subtly modified by the surface-molecule interaction. Accordingly, it was discovered that metallophthalocyanines and metalloporphyrins with 3d and 4f block metal centers exhibit remarkable electronic, optoelectronic, and magnetic properties when adsorbed on surfaces [1,2, [5][6][7][8][9][10][11][12][13][14][15][16]. Strikingly, the magnetic exchange coupling of the spin of metalloporphyrins or metallophthalocyanines with that of ferromagnetic (FM) substrates (Co and Ni) was found to induce stable magnetic order in the paramagnetic molecules at and above room temperature [1,2,11].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, the spin moment of the whole metalloporphyrin molecule decreases from 2.00 to 1.73 lB for the lipid-interacting molecule. It is noticeable that the net difference in the spin moment of the metalloporphyrin promoted by the association with the bilayer was higher than that described for in situ-sublimated Fe porphyrin molecules on ferromagnetic Ni and Co films on Cu(100) [64]. In this condition, the authors found a slight increase in the spin moment of the whole porphyrin molecule from 2.00 lB for the free molecule to 2.17 lB for the deposited molecule.…”
Section: Resultsmentioning
confidence: 76%